Detrended fluctuation analysis of leakage current characteristics of polyurethane insulators [Poliüretan Yalitkanlarin Sizinti Akimi Karakteristiklerinin Egimden Arindirilmis Dalgalanma Analizi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2018)
Polyurethanes are frequently employed as an insulation material in electrical networks based on their superior electrical and mechanical properties. The proper operation of electrical network depends strictly on insulation elements' performances. For this purpose, all insulation materials should be monitored and analyzed against electrical discharges and hence leakage currents which may lead to failure (breakdown) of the insulation. It is very challenging task to examine an insulator failure during electrical operation. In this study, the analysis of produced leakage currents on polyurethane samples is conducted by using a test setup which is operated based on IEC 60112 test standard. Detrended fluctuation analysis is proposed for investigating obtained leakage current signals, which exhibit nonlinear fluctuations. This analysis is employed for detecting the failure tendencies of the insulator by using leakage current signal characteristics. © 2018 IEEE.
Keywords: Detrended fluctuation analysis; Leakage current; Polyurethane insulator